The Adolescent HIV Treatment Bulge in South Africa’s National HIV Program: a retrospective cohort - Maskew, Mhairi (Lancet HIV, 2019)
BACKGROUND: The number of South African adolescents receiving HIV care and treatment in South Africa is growing. We used routinely collected laboratory data from South Africa’s National HIV Programme to: 1) quantify the numbers of adolescents accessing HIV care and treatment over time; 2) characterize the role of perinatal infection in these trends; and 3) estimate proportions of adolescents seeking HIV care and antiretroviral treatment (ART) in South Africa’s public sector. METHODS: National Health Laboratory Service (NHLS) conducts all laboratory monitoring for South Africa’s National HIV Programme. We conducted a descriptive cohort study of children and adolescents (aged 1-19 years) accessing care in South Africa’s public sector HIV treatment program from 2005-2016 with a CD4 count or viral load recorded in the NHLS database. We estimated the total number entering HIV care (number with CD4/viral load test result) by calendar period, as well as proportion in care and on ART (at least one VL test result). We stratified analyses by gender and by whether the patient entered care <15 years (likely perinatally infected) or at 15-19 years (likely infected in adolescence). FINDINGS: The cohort included 730,882 patients aged 1-19 years at entry to care. Fifty-four percent of patients (n=209,205) entering care <15 years were female while 88% (n=301,242) of those entering care aged 15-19 were female. During the study period, the number of virologically monitored ART patients aged 15-19 years increased 10-fold, from 7,949 in 2005-2008 to 80,918 in 2013-2016. Still, just two-thirds (n= 92,783/140,028) of 15-19-year olds seeking care started ART by 2016, well below UNAID’s target of ART for 90% of those diagnosed. We project the number of adolescents on ART will continue to rise. INTERPRETATION: Large increases in numbers of adolescents (aged 15-19 years) on ART reflect aging of children entering care at ages 1-14 years and increases in care-seeking care among 15-19 year-olds, presumably horizontally infected. However, many adolescents seeking care do not start ART, suggesting an urgent need for interventions to increase uptake of ART and improve services for this growing population.